Lake Victoria s eye-openers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Some 20 members of the cichlid fish family supposedly extinct - have adapted remarkably to the changed environment of Lake Victoria and are back in business. Scientists were surprised to learn in 1997 that local fishermen were catching cichlids...